(untitled) (Fiep Bulletin - online, 2014)
Objective: To identify occupational hazards present in the everyday activities of the Community Health Agent (CHA) to Cajazeiras-PB. Method: An exploratory study, the field with quantitative and qualitative approach and was conducted with 36 CHA (46.8% of the population). To obtain data we interviewed, whose questions were previously developed by authors themselves and having been previously validated and the data were analyzed using descriptive statistics and content analysis. Results: Showed that in relation to professional development, CHA displays so unsatisfactory team recognition and population in relation to their work. Regarding the difficulties in performing everyday activities at work, the lack of interaction with the staff and resources, increasing population and workload were the most mentioned elements. On the understanding of the occupational hazards they are exposed, most CHA displays the contact with contagious diseases, garbage, sun exposure, presence of disease-carrying animals or venomous and physical and mental violence that may occur at points of drugs. Conclusion: We realized the need for courses and training on health worker who can provide information that provide an effective process of self-care related to protection risks, which agents are exposed in their work environment.